Intrusion Detection System (IDS) with trusted nodes for improving security in Wireless Sensor Network - Jawahar, S; Adamkani, J (International Journal of Computer Sciences and Engineering, 2025)
Wireless Sensor Network (WSN) are the emerging and challenging technology with low processing and battery power. Security becomes a major issue in WSN; because of its wireless nature it is prone to various types of attacks and losing of data packet. Secure routing is important to avoid this type of issues. They are many techniques are available to provide secure routing to WSN. In the proposed work, our main aim is to find the trusted node and routing is done through the node to provide secure routing. The trusted node is identified by using Hidden Markov model (HMM) and it is rated. And also giving the un trusted node a chance to relay prove its identity. It provides the security features with minimum overhead and energy efficiency. The performance of proposed approach is illustrated that proposed model performs effectively compared with other existing approaches. Results demonstrated that developed HMM with trusted node provides significant performance in terms of memory overhead, delay, and Packet delivery ratio and energy consumption.